The Joe Brown Memorial Issue. - French, Nick (Emerald Group Pub., 2004)
As many of you will know, Gerald Brown died in May 2002 following a heroic, and always good spirited, fight against cancer. Gerald was the co-editor of this journal from 1999 and he was instrumental in steering the editorial policy during his short tenure. Previously published in: Property Investment and Finance, Volume 22, Number 6, 2004.